Comparative genomic and functional analyses of Paenibacillus peoriae ZBSF16 with biocontrol potential against grapevine diseases, provide insights into its genes related to plant growth-promoting and biocontrol mechanisms - Yuan, Lifang; Jiang, Hang; Jiang, Xilong; Li, Tinggang; Lu, Ping; Yin, Xiangtian; Wei, Yanfeng (Frontiers in Microbiology, 2022)
Paenibacillus peoriae is a plant growth-promoting rhizobacteria (PGPR) that is widely distributed in various environments. P. peoriae ZBFS16 was isolated from the wheat rhizosphere and significantly suppressed grape white rot disease caused by Coniella vitis. Here, we present the complete genome sequence of P. peoriae ZBFS16, which consists of a 5.83 Mb circular chromosome with an average G + C content of 45.62%. Phylogenetic analyses showed that ZBFS16 belongs to the genus P. peoriae and was similar to P. peoriae ZF390, P. peoriae HS311 and P. peoriae HJ-2. Comparative analysis with three closely related sequenced strains of P. peoriae identified the conservation of genes involved in IAA production, phosphate solubilization, nitrogen fixation, biofilm formation, flagella and chemotaxis, quorum-sensing systems, two-component systems, antimicrobial substances and resistance inducers. Meanwhile, in vitro experiments were also performed to confirm these functions. In addition, the strong colonization ability of P. peoriae ZBFS16 was observed in soil, which provides it with great potential for use in agriculture as a PGPR. This study will be helpful for further studies of P. peoriae on the mechanisms of plant growth promotion and biocontrol.